PENGARUH RISIKO BISNIS DAN RISIKO KEUANGAN TERHADAP TINGKAT KEUNTUNGAN (Studi Kasus Perusahaan Makanan dan Minuman di Indonesia) - Zainuddin - (Jurnal Akuntansi Muhammadiyah (JAM), 2013)
This research was aimed to examine the influence of business risk and financial risk against profit rate of food and beverage company in Indonesia. Profit rate is measured by return on investment (ROI) and return on equity (ROE). Observation period in the research from 2008 to 2011 financial statements have been audited food and beverage company listed on the Indonesia Stock Exchange, and the company reports its financial statements during period of research a total of 17 companies, and a the amount of observations were 68. Data analysis techniques used multiple linear regression. The results showed that the business risk and financial risk are jointly or partial effect on the rate of profit, both the rate of profit is measured by ROI and ROE in the food and beverage company in Indonesia. Keywords: Rate of return, return on investment, return on equity, business risk and financial risk.